Should imaging be a component of rheumatoid arthritis remission criteria? A comparison between traditional and modified composite remission scores and imaging assessments. Issue 5 (17th January 2011) - Saleem, Benazir; Brown, Andrew K; Keen, Helen; Nizam, Sharmin; Freeston, Jane; Wakefield, Richard; Karim, Zunaid; Quinn, Mark; Hensor, Elizabeth; Conaghan, Philip G; Emery, Paul
Objectives: Patients can fulfil clinical criteria for remission, yet still have evidence of synovitis detectable clinically and by ultrasound, and this is associated with structural damage. Stricter remission criteria may more accurately reflect true remission (no synovitis). This hypothesis was examined by studying patients using more stringent thresholds for clinical remission and determining their levels of ultrasound synovitis. Methods: Rheumatoid arthritis patients with a disease activity score in 28 joints (DAS28) ≤2.6 for at least 6 months were classified using standard and more stringent DAS28 and simplified disease activity index (SDAI) remission thresholds and the corresponding clinical and ultrasound imaging measures of synovitis recorded. Results: 128 patients (all DAS28 <2.6, median DAS28 1.70) receiving either disease-modifying antirheumatic drugs alone (n=66) or with a tumour necrosis factor blocker (n=62) were recruited. Of the 640 imaged joints, 5% had moderate or severe power Doppler (PD) activity, 8% were clinically swollen and 1% tender. In patients fulfilling DAS28, American College of Rheumatology or SDAI remission criteria, moderate or severe PD activity was present in 21%, 15% and 19%, respectively. More stringent DAS28 and SDAI criteria reduced the mean number of swollen and tender joints (p<0.001) but not the percentage of patients with PD activity: 32 patients had a DAS28 <1.17 but eight (25%) had significant PD activity. Conclusion: Using more stringent remission criteria resulted in reduced signs and symptoms of inflammation, but the percentage of joints with PD activity was not reduced, even in those without signs or symptoms. These data suggest that clinical criteria are sufficiently insensitive to detect low but clinically relevant levels of inflammation accurately.